2009
DOI: 10.4049/jimmunol.0900707
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-146a Feedback Inhibits RIG-I-Dependent Type I IFN Production in Macrophages by Targeting TRAF6, IRAK1, and IRAK2

Abstract: Upon recognition of viral components by pattern recognition receptors, including TLRs and retinoic acid-inducible gene I (RIG-I)- like helicases, cells are activated to produce type I IFN and proinflammatory cytokines. These pathways are tightly regulated by host to prevent inappropriate cellular response, but viruses can down-regulate these pathways for their survival. Recently, identification of negative regulators for cytoplasmic RNA-mediated antiviral signaling, especially the RIG-I pathway, attract much a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
622
6
9

Year Published

2012
2012
2015
2015

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 677 publications
(660 citation statements)
references
References 47 publications
23
622
6
9
Order By: Relevance
“…Several investigators suggested that ET in human monocytes and mouse macrophages is associated with decreased TLR4-MyD88-IRAK complex formation, impairment of IRAK-1 activity, and TRAF6 expression (45)(46)(47)(48)(49). In this regard, miRNAs have emerged as an important regulatory mechanism for gene expression of a number of TLR4 pathway components during ET (49); in particular, miR146a is critical for ET development in human monocytes (48,(50)(51)(52)(53)(54). As shown in Fig.…”
Section: Potential Intracellular Signaling Implicated In Et: the Rolementioning
confidence: 98%
“…Several investigators suggested that ET in human monocytes and mouse macrophages is associated with decreased TLR4-MyD88-IRAK complex formation, impairment of IRAK-1 activity, and TRAF6 expression (45)(46)(47)(48)(49). In this regard, miRNAs have emerged as an important regulatory mechanism for gene expression of a number of TLR4 pathway components during ET (49); in particular, miR146a is critical for ET development in human monocytes (48,(50)(51)(52)(53)(54). As shown in Fig.…”
Section: Potential Intracellular Signaling Implicated In Et: the Rolementioning
confidence: 98%
“…The regulatory mechanisms of the RIG-I signaling pathway are similar to the ones described above, although the regulation has not yet been clearly defined. 70 These data indicate that the immune system utilizes multiple miRNAs to properly regulate its functional capacity, creating a finely tuned balance between activation and repression. Nonetheless, the precise regulatory roles of miRNAs in TLR and RIG-I responses are still not fully understood, especially how these miRNA networks collaborate together to optimize immune responses.…”
Section: Mirna-mediated Regulation Of Rig-i Signaling Pathway and Virmentioning
confidence: 99%
“…Recently, IRAK2, a kinase that compensates for IRAK1 to activate NF-kB, has also been confirmed as a miR-146 target. 70 Other key TLR signaling pathway components have also been demonstrated as miRNA targets. MyD88 adaptor-like protein, which functions as a bridge for the TLR2 and TLR4-mediated MyD88-dependent pathway, has emerged as a miR-145 target, 80 although the miR-145 expression profile following TLR agonist stimulation remains undetermined.…”
Section: Mirnas In Regulation Of Tlr and Rig-i Pathways Yk LI And Xymentioning
confidence: 99%
See 2 more Smart Citations